2008
DOI: 10.17221/3/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of α-galactosides during the germination of grain legume seeds

Abstract: Kadlec P., Dostálová J., Bernášková J., Skulinová M. (2008): Degradation of α-galactosides during the germination of grain legume seeds. Czech J. Food Sci., 26: 99-108.Germination is one of the most effective ways of preparing grain legumes for consumption. Because it involves the total or partial elimination of some anti-nutritional compounds, it is also one of the simplest methods of enhancing the palatability of grain legumes, thereby increasing their consumption as a valuable source of nutrition. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Our data also indicate presence of considerable amounts of galactosyl pinitols (accounting for 13% of TSCs, Table 1), with prevalent GPA (Online Resources, Table 1). Changes in the concentrations of RFOs, sucrose and monosaccharides in germinating fenugreek seeds, found in our study (Table 1), correspond well with the results obtained earlier by Dirk et al (1999) and are generally similar to the ones occurring in germinating legume seeds (Górecki et al 2000;Kadlec et al 2008;Martin-Cabrejas et al 2008). Moreover, the fast degradation of galactosyl cyclitols confirms their role as reserve materials important for early germination of fenugreek seeds, same as in seeds of winter vetch (Lahuta and Goszczyńska 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Our data also indicate presence of considerable amounts of galactosyl pinitols (accounting for 13% of TSCs, Table 1), with prevalent GPA (Online Resources, Table 1). Changes in the concentrations of RFOs, sucrose and monosaccharides in germinating fenugreek seeds, found in our study (Table 1), correspond well with the results obtained earlier by Dirk et al (1999) and are generally similar to the ones occurring in germinating legume seeds (Górecki et al 2000;Kadlec et al 2008;Martin-Cabrejas et al 2008). Moreover, the fast degradation of galactosyl cyclitols confirms their role as reserve materials important for early germination of fenugreek seeds, same as in seeds of winter vetch (Lahuta and Goszczyńska 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Kadlec, Dostalova, Bernaskova, & Skulinova, (2008) modelled the degradation of alpha-galactosides during the germination of legume seeds (mung bean, chickpea, and lentil) using zero-order, first-order kinetic reactions as well as empirical equations. Their results showed that the best fit was obtained using empirical equations, which do not provide any information about the mechanisms underlying alpha-galactoside degradation.…”
Section: Introductionmentioning
confidence: 99%
“…There was no interaction between lines and years of experiments (significance of lines × year interaction, F statistic > 0.01). The RFO concentration in seeds of various legume species ranges, on a dry matter (DM) basis, from 2.4-3.5% in broad bean, lentil and chickpea (Górecki et al 2001;Kadlec et al 2008) up to 11-16% in yellow lupine (Martinez-Villaluenga et al 2008). Pea has one of the highest levels of oligosaccharide content among legumes -from 2.3 to 9.6% DM (Martinez-Villaluenga et al 2008).…”
Section: Resultsmentioning
confidence: 99%